Journalistic role performance – the Hungarian case - Szabó, Gabriella; Kormos, Nikolett; Zagyi, Veronika (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2016)
The article introduces the results of an empirical examination of journalistic role performance in Hungary. In reference to the “Journalistic Role Performance Around the Globe” research project (led by Prof. Claudia Mellado from Pontificia Universidad Católica de Valparaíso, in Chile and Lea Hellmueller, from Texas States University, www.journalisticperformance.org), we attempt to discuss the main patterns of role performance in contemporary journalism in Hungary. The presence of six models in news production (watchdog, disseminator-interventionist, civic, loyalfacilitator, service journalism, and infotainment) is investigated by conducting a quantitative content analysis of 1,087 news items published by the national desk of four Hungarian broadsheets in 2012–2013.
Keywords: journalism; role performance; quantitative content analysis; Hungary